EFFECT OF MENOPAUSE AND LIFESTYLE FACTORS ON SERUM VITAMIN D STATUS IN POSTMENOPAUSAL WOMEN - ALI, FARHA; MANINDER BINDRA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The study was designed to determine the effect of menopause and lifestyle factors on Serum Vitamin D levels in postmenopausal women. Methods: The present study comprises 100 healthy women treated as controls and was compared to 200 postmenopausal women as cases. Those fulfilling inclusion and exclusion criteria were enrolled for the study and blood samples were analyzed for Vitamin D and Estrogen. Results: Significant lower concentration of Vitamin D (p<0.001) and estrogen (p<0.001) was found in postmenopausal women when compared with healthy women. Conclusion: Vitamin D is a steroid hormone known for its essential role in maintaining calcium homeostasis, promoting and maintaining bone health, and improving immune function. During the menopausal stages, there is a gradual reduction in estrogen levels this decline in estrogen production promotes Vitamin D deficiency.